Pattern of adverse drug reactions occurring at department of neurology of a tertiary care hospital in India - Kushwaha, Virendra; Agrawal, Pooja; Srivastava, Ruchi; Verma, Alok (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective of the study was to study the pattern and trends of adverse effects of drugs used in department of neurology in a tertiary care hospital. Methods: A prospective, observational study was carried out for a duration of 12 months from November 2018 to October 2019 at Department of Neurology and Department of Pharmacology and Therapeutics, G.S.V.M. Medical College, Kanpur after getting an approval from institutional ethical committee. Data was collected by analyzing OPD prescription slip, treatment charts and investigation reports. All relevant information regarding adverse drug reactions (ADRs) were collected as per norms of Indian Pharmacopoeia commission (IPC). Results: During the study period, a total of 130 ADRs reported. Most of the ADRs were reported due to antiepileptic drugs followed by antiparkinsonian drugs. Dizziness was the most frequent ADR reported. Most of the ADRs were reported due to phenytoin. Other ADRs observed were drowsiness, nausea/vomiting, weakness, joint pain, dyskinesia. Conclusions: Most of the ADRs were due to anti-epileptic drugs. Most of the reactions were of mild severity.